Determinantes de la morosidad crediticia del sistema financiero de Loreto periodo 2017 – 2021 - Navas Solignac, Giannina Liliany (2024)
This study analyzes the determinants of credit default in the financial system of Loreto from 2017 to 2021. The general hypothesis posits that inflation rate and loan placements level are significant factors in default. A multiple linear regression model is proposed to test this hypothesis, incorporating these variables along with others such as the active interest rate, the number of financial agencies, and the error term. Individual significance tests, like the student’s t-test and the p-value test, are employed to verify the statistical significance of the variable coefficients. It is assumed that the independent variables are exogenous to the error term, using the method of ordinary least squares estimation. The results indicate that all candidate variables are significant, suggesting that both the inflation rate and loan placements level, active interest rate, and the number of financial agencies are determinants of credit default in Loreto.